Study on Energy Efficiency and Harmonic Emission of Photovoltaic Inverters - Krzysztof Chmielowiec; Łukasz Topolski; Aleks Piszczek; Tomasz Rodziewicz; Zbigniew Hanzelka (Energies, 2022)
The paper presents the results of an experimental study of 26 brand new photovoltaic (PV) inverters widely available for sale on the EU market; the study was conducted in 2021 by researchers at the AGH University of Science and Technology and Tauron Dystrybucja (Polish DSO). The purpose of the study was to compare and assess PV inverter performances in terms of their DC/AC conversion efficiencies, MPPT efficiencies, and harmonic current emissions. To examine the PV inverters, a laboratory test stand was prepared according to the standard EN 50530 and the technical report IEC/TR 61000-3-15. It was composed of a photovoltaic array simulator, a programmable regenerative AC voltage source, and a power analyzer. Each PV inverter was tested in various operating states determined by the DC voltage levels and the volume of active power generation. The results allowed for a benchmark assessment of PV inverters available on the market. The results showed how various energy efficiency indicators of individual PV inverters changed depending on their operating points. The results also revealed that, based on the performed harmonic emission tests, individual harmonics were within the normative requirements; however, in the case of several PV inverters, attention was drawn to the presence of relatively high switching frequency-related components exceeding permissible levels.